Treatment Algorithm for Hyaluronic Acid-Related Complication Based on a Systematic Review of Case Reports, Case Series, and Clinical Experience. Issue 4 (December 2020) - Aviv, Uri; Haik, Josef; Weiss, Nathaniel; Berl, Ariel; Ofir, Hagit; Nardini, Gil; Cleary, Michelle; Kornhaber, Rachel; Harats, Moti
Study Design: Systematic review of hyaluronic acid (HA)-related complications. Objective: To systematically review all available literature including case reports and case series to identify a pattern for the management of vascular compromise resulting in facial skin ischemia and ocular manifestations following HA injection. Methods: This review was based on a systematic search of 3 electronic databases PubMed, CINAHL, and Scopus for all available literature including case series and case reports from database inception to July 2019. Only a total of 52 case reports/series were eligible for review and included 107 patients. Results: The reviewed literature available was comprised from case reports/series and indicated that management of both impending skin necrosis and visual disturbances is variable with no repetitive pattern of action. Yet, successful management is time dependent as early interventions stopped progression and, in some cases, even reversed adverse effects. Conclusion: Results found no universal protocol for achieving optimal results for adverse effects and as such, we present a step-by-step algorithm for the emergency management of complications following HA injection.